The Dynamics of the Sensitive Sense. Feeling, Sensing, Perceiving and Conceiving - Moutat, Audrey (Semiotika, 2023)
Based on the various semiotic works devoted to the sensory world and to perception, this article proposes to retrace the generative path of sensory meaning from the immediate perception to its conceptualization. The aim is to highlight not only the constitutive dynamics of the semioses involved in this journey, but also the complex relationships involved in the emergence of sensitive signification. In order to do this, we will return to the constitutive principles of the plan of expression of perceptual semiosis and the dynamics that animate it, before determining their role in the articulation of sensory meaning. In this way, the concept of structure will prove decisive in uncovering a theory of knowledge of the sensible world. We shall see that, from icon to diagram, structure is the object of an abstractive operation that reconfigures not only phenomena and their tensive dynamics, but also the intentional variations of subjects that are functionally associated with them. In this respect, we will underline the importance of the elementary contrast in the classification of the perceived and the construction of the concept, understood as a prototypical example of the class. Finally, we will raise the profoundly unstable character of the perceptual semiosis and the influence games that constantly renegotiate the elementary meaning of the sensory.